Effect of vitamin E on the immune system of SPF birds vaccinated against infectious bronchitis virus - De Almeida J.M.* (2014)
In order to analyze the influence of vitamin E on the immune response of birds vaccinated and challenged with Infectious Bronchitis Virus in poultry (IBV), and which dose of vitamin E is the best to answer this, an experiment was conducted using 50 SPF birds housed with one day of life at Embrapa - Suínos e Aves. All birds were divided into 10 groups of five birds each, including positive and negative control groups, supplemented with 15, 50, and 200 IU of vitamin E/Kg added into the feed. On the 14th day of life the birds were vaccinated with a commercial vaccine for infectious bronchitis (H-120) and after 28 days, one group for each treatment was challenged with IBV, strain classical (M-41). Five days after challenge birds were necropsied and abdominal macrophages were collected for analysis of microbicidal activity and measurement of nitric oxide (NO). The lung was collected for cell count by flow cytometry and also for NO dosage. Organs of predilection were also collected for histological analysis and virus isolation to analyze the efficiency of the vaccine. The results were evaluated by ANOVA and Student t-test. An increased of microbicidal activity of abdominal macrophages was observed in the groups of birds with higher levels of vitamin E (200 IU/Kg) supplementation when compared with groups that did not receive or received minor amounts (0, 15, 50 IU/Kg), indicating an improvement in the innate immune response influenced by vitamin E supplementation in the diet. The supplementation of this vitamin in high doses also increases the ability of macrophages to produce NO. And, by flow cytometry, suggests that the macrophages are the primary cells recruited in the lung tissue to combat infectious bronchitis and this action was potentiated by the addition of vitamin E, independent of the dosage.